Comparative clinical and economic analysis of pozaconazol (Noxafil) for invasive mycoses (IM) prevention in patients with severe neutropenia during treatment of acute myeloid leukemia or myelodysplastic syndrome - I. S. Krysanov; N. N. Klimko; V. Yu. Ermakova; V. S. Krysanova (Онкогематология)
Objective: a comparative clinical and economic analysis of posaconazole (Noxafil) for invasive mycoses (IM) prevention in patients with severe neutropenia during treatment of acute myeloid leukemia or myelodysplastic syndrome in Russia. Materials and methods. A model was constructed that takes into account the use of various mediactions: posaconazole, voriconazole and fluconazole. Cost estimation for IM prevention was carried out considering the direct medical costs of IM prevention, IM therapy, hospital stay, therapeutic and diagnostic procedures and monitoring in case of IM. “Cost–effectiveness” and “budget impact” analyzes were performed. Results. Based on literature data, high efficacy and safety of posaconazole for IM prevention in patients with severe neutropenia during treatment of acute myeloid leukemia or myelodysplastic syndrome was shown. Cost analysis of drugs showed the lowest total costs for IM prevention with posaconazole – 185,745.49 rubles, followed by fluconazole – 275,360.26 rubles, and voriconazole – 299,792.76 rubles. At the same time, in the structure of total costs, for posaconazole and voriconazole, the cost of IM prevention prevailed – 155,017.17 rubles and 156,393.92 rubles, respectively, whereas for fluconazole – the costs of IM treatment – 168,390.45 rubles. This is due to the significantly higher incidence of IM cases in fluconazole group compared with posaconazole and voriconazole. The use of posaconazole also showed the best ratio of cost–effectiveness for one prevented case of infection and for one extended year of the patient’s life (191,490.20 rubles and 34,980.32, respectively). Due to lowest costs and best efficiency of posaconazole, the incremental cost– effectiveness ratio (ICER) was not calculated. Thus, the use of posaconazole for IM prevention in acute myeloid leukemia patients can reduce the overall cost per patient by 114,047.27 rubles compared with voriconazole and by 89,614.76 rubles compared with fluconazole. The sensitivity analysis for cost–effectiveness results demonstrated the stability of IM prevention model in acute myeloid leukemia patients to changes in the initial posaconazole price upwards to +61 %. The model has the highest sensitivity to IM incidence with unsuccessful prevention. “Budget impact” analysis of IM prevention in acute myeloid leukemia patients older than 13 years in Russia showed that an increase in the posaconazole proportion from 25 to 50 % with a decrease of voriconazole proportion from 25 to 15 % and fluconazole proportion from 50 to 35 % in government procurement will reduce budget costs by 48.1 million rubles. The sensitivity analysis for “budget impact” results showed the greatest sensitivity to changes in the patient number and to increase of posaconazole proportion in procurement. Results were less sensitive to an increase of voriconazole and fluconazole proportion. Conclusion. The results of the study showed that the use of posaconazole for the prevention of invasive mycoses in patients with severe neutropenia during treatment of acute myeloid leukemia and myelodysplastic syndrome is clinically effective and economically justified within the system of state preferential drug provision in the Russia.